Diversity analysis, identification, and bioprospecting of Lactic Acid Bacteria (LAB) isolated from Sumbawa horse milk - KHADIJAH ALLIYA FIDIEN; Baso Manguntungi; LINDA SUKMARINI; APON ZAENAL MUSTOPA; LITA TRIRATNA; FATIMAH FATIMAH; KUSDIANAWATI KUSDIANAWATI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Fidien KA, Manguntungi B, Sukmarini L, Mustopa AZ, Triratna L, Fatimah, Kusdianawati. 2021. Diversity analysis, identification, and bioprospecting of Lactic Acid Bacteria (LAB) isolated from Sumbawa horse milk. Biodiversitas 22: 3333-3340. Sumbawa horse milk has a probiotic potential because of the presence of Lactic Acid Bacteria (LAB). The LAB present in Sumbawa horse milk has been reported to have antimicrobial activities against pathogenic bacteria, including Staphylococcus epidermidis, Staphylococcus aureus, Escherichia coli, and Vibrio cholerae. However, the potential of LAB from Sumbawa horse milk as antioxidant and antidiabetic is still unexplored. Studies related to the diversity of indigenous bacteria in Sumbawa horse milk based on metagenomic analysis have not been widely studied either. Therefore, this study aimed to determine the diversity of species of indigenous bacteria in Sumbawa horse milk and to identify LAB bioprospecting from Sumbawa horse milk. The diversity of indigenous bacterial species was investigated by the 16S rRNA gene-targeted metagenomic approach from bacterial DNA isolated from Sumbawa horse milk. The identification of LAB was also carried out by the 16S rRNA gene identification method. LAB bioprospecting on antioxidant activity was determined using the DPPH method, while the antidiabetic activity was measured using the ?-glucosidase inhibition assay. The diversity analysis of indigenous bacteria based on 16S rRNA gene-based metagenomic revealed at least 7 phyla were relatively abundant in Sumbawa horse milk. The greatest abundance was shown by the phylum Proteobacteria (0.641%) and Firmicutes (0.327%). Enterococcus durans (39.01%) was the species that had the highest abundance in Sumbawa horse milk, followed by Lactococcus garvieae (30.13%) and Lactococcus lactis (19.85%). Moreover, based on the identification of the 16S rRNA gene, eight LAB isolates had similarities to bacterial strains, including Enterococcus faecium DSM 20477, E. faecium NBRC 100486, E. faecium ATCC 19434, E. durans 98D, E. faecalis ATCC 19433, E. faecalis NRBC 100480, Lactococcus lactis subsp. hordniae NBRC 100931 and L. garvieae JCM 10343 with similarity levels of more than 98%. In terms of LAB bioprospecting, the antioxidant assay showed the highest DPPH radical binding activity by L. garvieae L.22PR (43%). Meanwhile, the highest inhibitory activity of ?-glucosidase was shown by E. faecium G.6PR (45%).